The Chukchee. Memoirs of the AMNH - Bogoras, Waldemar, 1865-1936. (Leiden, E.J. Brill ltd.; New York, G.E. Stechert, 1904)
3 v. : illus., 35 pl., fold. map. 36 cm. "Authorities quoted": p. 3-9. pt. 1. Material culture. 1904 -- pt. 2. Religion. 1907 -- pt. 3. Social organization. 1909.